Judaism and views criticism of sacred Scripture in the Arabic speaking sources - Abdyhalyk, A. E. (Journal of Oriental Studies, 2016)
This article discusses the concept of religious Judaism in the Arabic speaking sources. Indicates the relevance of the study of the sources of Jewish themes in the Arabic language, and also offer to divide the study period into two periods.